Romance in the cloud: Interpersonal communication analysis on relationship stages of online dating - Rahmawati; Unde, Andi Alimuddin; Bahfiarti, Tuti (Universitas Islam Malang, 2023)
Finding love in the digital age can be seen easier than ever. With a simple app, an individual and millions of others can come together and meet from everywhere. The researchers aim to analyze the relationship development in online dating matches through multiple interpersonal communication perspectives. It includes how an individual chooses their potential partner, their initial involvement, self-disclosure, and whether they decide to continue a serious relationship. The research methodology used is qualitative method with in depth interview, using Devito’s Relationship Stages as the theoretical framework. The result shows that compared to traditional dating, online dating couples took extra security precautions in early contact. It is also found that the strength of social bonding, especially with close friends and family members, significantly influences the relationship. There are three main stages of relationships that are experienced in this research; (1) Contact, in line with the Uncertainty Reduction Theory and Communication Privacy Management, (2) Involvement that corresponds with the Social Exchange Theory, and (3) Intimacy, that aligns with Social Penetration Theory.